PENGGUNAAN APPSHEET BERBASIS ANDROID ABSENSI KEHADIRAN GURU DI SEKOLAH DASAR NEGERI 65 KOTA BENGKULU - WALAD; Apridiansyah, Yovi (JPMTT (Jurnal Pengabdian Masyarakat Teknologi Terbarukan), 2025)
The advancement of information technology has extended to various sectors, including education. The manual attendance system at SD Negeri 65 Kota Bengkulu has several drawbacks, such as data loss risks, inefficiency in recap processing, and limited attendance reporting. Therefore, digitalizing the attendance system is essential to enhance accuracy, efficiency, and transparency in recording teachers' and staff attendance. This study aims to develop an Android-based attendance application using AppSheet as a solution for schools to improve work discipline and streamline administrative processes. The application development is conducted as part of the Internship Program (PKL) for undergraduate students of the Computer Science Program at Universitas Muhammadiyah Bengkulu. The resulting application enables digital attendance recording, integration with reporting systems, and real-time access to attendance data. This system is expected to optimize attendance management and enhance the performance of educators. Furthermore, this research can serve as a reference for other schools considering adopting similar technology.